Six-Pack Balancing Act: A Conceptual Model for the Intestinal Lining - PK Rangachari (Canadian Journal of Gastroenterology)
The cells chat form the lining of the intestine belong to a class of cells termed 'polarized' or 'asymmetric.' The membranes surrounding these cells show functional differences at the luminal and contraluminal surfaces. The cells line up to form sheets and it is across these sheers that movement of fluids and solutes occurs. Such movement occurs in both directions across the lining and the occurrence of diarrhea or constipation depends to a considerable extent upon the net result of the absorptive and secretory mechanisms and their modulation by a host of factors such as neurotransmitters, bacterial products, drugs, etc. This review provides a simple framework for understanding the dynamics of the gut lining. Diamond's six-pack model of epithelia is modified to include the dynamic tension between absorptive and secretory mechanisms.